Interpretasi dan Ekspresi Solis French Horn, Saxophone, Seruling, Trumpet pada Repertoar O Tano Batak - Heppi Malau; Hafif HR; Nursyirwan Nursyirwan (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Success in a musical performance cannot be separated from the ability of a presenter to bring works in accordance with the art and beauty of music made by a composer. Research with the title Interpretation and Expression of Solis French Horn, Saxophone, Flute, Trumpet in the O Tano Batak Performance in the aspect of sound color. In this study, the authors use the concept of interpretation in the concept of sound color, as well as in wind instruments. The second concept is a visual concept, namely expression. O Tano Batak's work has differences in each part. In compiling the design of the presentation of the music used, namely French Horn, Saxophone, Flute and Trumpet. The techniques for playing each instrument that must be prepared, both ambouchure and fingering techniques in interpreting the demands contained in the musical repertoire and presentation in the form of musical performances to the audience or audience. This writer aims to reveal what abilities should be carried out technically in playing French Horn, Saxophone, Flute, Trumpet in interpreting a musical repertoire with different musical styles and how to present this musical repertoire to the audience in a French Horn Solis performance, Saxophone, Flute, Trumpet accompanied by Combo Band.